PEMBUATAN WEBSITE UNTUK SOSIALISASI PROGRAM DAN BERITA PELAKSANAAN KEGIATAN PADA YAYASAN BUMI LANGGAT PEDULI - Yoppy Yunhasnawa; Toga Aldila Cinderatama; Moch. Zawaruddin Abdullah; Gunawan Budiprasetyo; Muhammad Afif Hendrawan; Candra Bella Vista; Rinanza Zulmy Alhamri; Maskur Maskur (Jurnal Pengabdian kepada Masyarakat, 2023)
Yayasan Bumi Langgat Peduli, based in Dusun Langgat, Malang, is a community initiative since 2017, focusing on social development. With funding sources from donors and the "Bongkar-Rapikan-Sedekahkan" program, the foundation has conducted various inclusive programs. However, manual communication via WhatsApp limits the reach of information. Through the Community Engagement project, we from Politeknik Negeri Malang design, implement, and deploy an official website that not only expands the information reach but also effectively showcases the foundation's programs and activities. This endeavor encapsulates a comprehensive solution to enhance Yayasan's outreach and impact.